HUBUNGAN TINGKAT RELIGIUSITAS DENGAN TINGKAT STRES PADA MAHASISWA KEPERAWATAN SAAT MENGHADAPI UJIAN SKILL LAB - Khairunnisa Fitri de Firda; Jumaini Jumaini; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The level of stress experienced by students can be influenced by various factors, one of which is the level of religiosity. This study aimed to determine the relationship between the level of religiosity with the stress level of nursing students when facing the skill lab test. This study used a descriptive correlation design and a cross sectional approach. The research sample was 200 respondents who were taken based on the inclusion criteria using proportionate stratified random sampling technique. The analysis used is bivariate analysis using chi-square test. There are 122 respondents who have a high level of religiosity (61.0%), as many as 107 respondents have a stress level in the moderate category (53.5%). stress on nursing students when facing the skill lab with p value (0.364) > alpha (0.05). There is no relationship between religiosity levels and stress levels in nursing students when facing the skill lab test. Based on research obtained, it is certain that students who feel stressed when facing the skill lab test to improve and optimize other factors such as psychological factors, environmental factors and physical factorsKeywords: religiosity, skill lab test, stress, students